Evaluation of Hazelnut Shells in Polypropylene Based Polymer Composite Production - Karim Yildirim (International Journal of Science and Society, 2020)
Natural fibers have been commonly utilized to reinforced materials for many years. Recently due to advantages of natural fibers such as low cost, high physical and mechanical resistance are produced plastic-composite materials by mixing various proportions. In addition, plastic composites are used natural fibers include agricultural wastes (wheat straw, rice straw, hemp fiber, shells of various dry fruits, etc.). In this study, polymer composites were manufactured using waste nutshell flour as filler and polypropylene (PP) as polymer matrix. The nutshell-PP composites were manufactured via extrusion and compression methods. The final product tested to determine their tensile, flexural, impact strength properties as well as some physical features such as thickness swelling and water absorptions. The best results were obtained composites containing 30% nutshell flour. In addition, composites which were produced nutshell provided the values of ASTM D6662 standard. The data collected in our country which waste a large portion of nutshell allows for the evaluation of the production polymer composites. The incorporation of nutshell flour feasible to produce plastic composites when appropriate formulations were used. As a result hazelnut shell which was considered agricultural waste can be utilized in polymer composite production.